Frequency domain modelling of transversely isotropic viscoelastic fibre-reinforced plastics - Liebig, Wilfried V.; Jackstadt, Alexander; Sessner, Vincent; Weidenmann, Kay A.; Kärger, Luise (Composites science and technology, 2019)
The subject of this work is the development of an approach describing the transversely isotropic viscoelastic material behaviour of carbon-fibre-reinforced plastics (CFRP) in the frequency domain. To identify the composite's macro-scopic transversely isotropic viscoelastic material behaviour, micro-scale numerical studies are performed on statistically representative volume elements (SRVE) under periodic boundary conditions to obtain master curves of five independent components of the homogenised complex stiffness tensor in the frequency domain. These homogenised properties are then depicted by a generalised and by a generalised fractional Maxwell model (GMM, GFMM) building the dataset for parametrising user-defined material models implemented in commercial finite element method (FEM) software. The material models are thus able to capture the material behaviour over multiple orders of magnitude in frequency with a single set of parameters each. Consequently, the conversion of time-dependent data is avoided. A comparison between experimental and numerical results is carried out and further studies on the influence of the fibre volume content are performed. The proposed method is found capable of characterising the viscoelastic behaviour of CFRP in the frequency domain and, thus, presents a viable tool to investigate e.g. the damping characteristics of fibre-reinforced plastics on component level.